The Role of Strategy Use Instruction in Improving EFL Learners’ Integrated Writing Ability and Their Affective State: A Mixed-Methods Study - Farhang Daneshfard; Mahboobeh Saadat (Journal of Modern Research in English Language Studies)
The integration of reading and writing has recently been of interest to researchers. This study investigated the effectiveness of instructing integrated writing (IW) strategies to EFL learners. In addition, the changes in writing self-efficacy, anxiety, and motivation were examined. To gain a deep understanding of the issues, a convergent mixed-methods design was employed. A convenient sample of 30 students of English Literature studying in an EFL context participated in an IW course and their performances before and after instruction were compared using a rubric. Interviews and thinkaloud protocols were also conducted to find themes regarding the effectiveness of the course. Moreover, the changes in the learners’ selfefficacy, anxiety, and motivation were measured through questionnaires administered at the beginning and the end of the course, and the interviews and think-aloud protocol themes regarding the changes were examined. The results of the analysis of the quantitative data by paired-samples t-tests and Wilcoxon Signed Rank tests indicated an improvement in the learners’ IW ability and strategy use, especially in source use. The qualitative data also revealed that the learners found the instruction and strategies effective. However, while the learners’ self-efficacy improved and their anxiety diminished largely due to learning, their motivation remained statistically stable. The results were interpreted from an activity theory perspective. The implications of the study for the theory, pedagogy, and research methodology of IW were also presented.